Investigation of flow growth in a duct flows for higher area ratio - Aabid, Abdul; Khan, Sher Afghan; Baig, Maugal Ahmed Ali; Reddy, Avala Raji (IOP Publishing, 2021)
Base pressure is a crucial factor in evaluating flow parameters. The effect of the flow regulation mechanism is through an experiment examined for the convergent-divergent (C-D) nozzle with abrupt enlargement in an axisymmetric duct. The microjet control is extended along the nozzle's exit diameter at a 90-degree interval having a circular cross-section in the shape of an orifice of 0.5 mm radius. This research's primary aim is to evaluate the flow quality near the wall in the absence and presence of control. The experimental investigation aims to record the data for area ratio 6.25 of the flow field at the separate flow zone's rear end. At ninety degrees apart, four tiny jets are situated at 6.5 mm from the axis of the primary shear layer emanating from the nozzle. The small control jets attain critical conditions. The real Mach values for the main jets were 1.1 and 1.5, respectively, in the present study. The experiments were done at different expansions in the range from 11 to 3. The duct length was in the range of 10 to 1. This research primarily aims to study the quality of the duct's flow and its influence on the pressure and the pressure level along the duct. It is realized that the duct pressure is not harshly affected by the control jets in the pipe founded on the current findings.